Elaboración de un manual de funcionamiento, mantenimiento y plan de renovación de los equipos: destilador, mufla, espectrofotómetro y equipo soxhlet, para el laboratorio de análisis y control de alimentos de la carrera de Ingeniería Agroindustrial de la Universidad Técnica de Cotopaxi , en el periodo 2012 – 2013. - Llango Guamishi, Milton Ramiro (2013)
The present research is focused on the designing functioning, maintenance manual and renewal plan equipment: distiller, muffler, spectrophotometer and soxhlet equipment, for the food analysis and control laboratory of the Agro-industrial Engineering major at Technical University of Cotopaxi. The most optimal method for research has been searched and used to elaborate the manuals such as the practical-type and descriptive investigation. The compilation of information that used for the execution of the theoretical background and the manuals. The methodology used in this research job during the practice helped us to determine the functioning state of equipment and its condition of the operation. Each manual contains a detailed description of functioning, its components, generalities, required services for the proper functioning, maintenance type in which the routine, preventive, predictive and corrective maintenance is detailed. This research is complemented with the different types of maintenance that lead actions for calibration, adjustment, reparation and replacement components processes for a satisfying operation by the several practices activities.